INTELLIGIBILITY, COMPREHENSIBILITY, AND INTERPRETABILITY PROBLEMS IN THE INTERACTIONS BETWEEN LECTURERS AND STUDENTS IN ENGLISH DEPARTMENT PROGRAM - Author, Nailul; Tatik Mufliha (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
Intelligibility, comprehensibility, and interpretability come to be problems in classroominteraction. Those 3 components contribute to flow of interaction, comprehend the message delivered,and to learning objectives attainment.This recent study was conducted by using qualitative research, inwhich the participants were from 2 universities with 4 different classes. then the research objectivesshould be constructed; to identify the intelligibility, comprehensibility, and interpretation problems ininteraction between lectures and students; to investigate the extent of intelligibility,comprehensibility,and interpretation in facilitating lecturer-students communication; to depict students learning objectiveattainment by the practice of intelligibility, comprehensibility, and interpretation. This study usingQualitative research method. Purposes sampling was used in this study by choosing homogenous type.The data was collected through observation. Reading and analyzing references were able to sustenancethe research data about the notion.This study clarified that the intelligibility, comprehensibility, andinterpretability problems did not contribute significant problems to the participant due to the lecturerand the students are from same area, thus the cultural barriers were not be the core of barrier in thecommunication. It is more to the personal and interaction barriers of the students.